2019
DOI: 10.1371/journal.pone.0221794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed, management and personality on cortisol reactivity in sport horses

Abstract: Sport horses need to fulfill high physical and psychological requirements during training and competition. These as well as certain conditions of modern husbandry may affect their wellbeing. Here we aimed to (1) evaluate effects of demographic and management factors as well as personality traits on stress reactivity of sport horses, (2) investigate if elite sport horses have elevated stress levels compared to amateur sport horses, and (3) assess whether different equestrian disciplines differentially influence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
0
21
1
Order By: Relevance
“…In common with the other breeds used in the study, the TB/WB horses were a mixture of horses that were either in active training for eventing competitions or horses that had been in low to moderate exercise for at least the month prior to the experiment. In comparison to our data, Sauer et al, 102 reported that warmblood and thoroughbred sport horses had higher salivary cortisol concentrations in response to ACTH challenge than French-Montagne breed horses. Cortisol responsive phenotypes have been identified in Japanese quail 103 , mice 104 and cortisol reactivity in humans is associated with some psychiatric disorders 105 .…”
Section: Discussioncontrasting
confidence: 86%
“…In common with the other breeds used in the study, the TB/WB horses were a mixture of horses that were either in active training for eventing competitions or horses that had been in low to moderate exercise for at least the month prior to the experiment. In comparison to our data, Sauer et al, 102 reported that warmblood and thoroughbred sport horses had higher salivary cortisol concentrations in response to ACTH challenge than French-Montagne breed horses. Cortisol responsive phenotypes have been identified in Japanese quail 103 , mice 104 and cortisol reactivity in humans is associated with some psychiatric disorders 105 .…”
Section: Discussioncontrasting
confidence: 86%
“…As reported by Sauer et al [ 47 ], stress resistance may be related to the animal breed as well as maintenance and use of the animal. The high level of cortisol in the examined horses may be related to these indicators, which suggests a need for further research in this field.…”
Section: Discussionmentioning
confidence: 97%
“…Smeets et al [ 114 ] reported impaired cognitive flexibility in humans with higher salivary cortisol concentrations irrespective of stress exposure. To date, while breed differences in salivary cortisol have been identified [ 115 ], there is little data on whether cortisol genotypes per se exist in horses. Further research evaluating cortisol reactivity and cognition in horses is required to confirm our finding as other studies have reported either no relationship between salivary cortisol and task performance [ 116 ] or a transient increase in performance in an appetitive task acquisition in horses [ 117 ].…”
Section: Discussionmentioning
confidence: 99%